2004
DOI: 10.3102/0091732x028001101
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 4: African American Principals and the Legacy of Brown

Abstract: T he year 2004 was filled with celebrations and commemorations of the 50th anniversary of the Brown v. Board of Education decision. There were a significant number of conferences that featured experts from education, law, sociology, and civil rights organizations who spoke of promises fulfilled and unfulfilled 50 years after the historic decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 72 publications
(137 reference statements)
2
91
0
Order By: Relevance
“…For example, Black segregated schools (cf. Sowell, 1974;Walker, 1996Walker, , 2009aWalker, , 2009b are rightfully lauded for their strong interpersonal mechanisms, such as teacher-student relationships (Foster, 1990(Foster, , 1998Lomotey, 1989Lomotey, , 2003Tillman, 2004;Walker, 1996Walker, , 2000. Postdesegregation schools designed for…”
Section: The Relational Work Of Black Educatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Black segregated schools (cf. Sowell, 1974;Walker, 1996Walker, , 2009aWalker, , 2009b are rightfully lauded for their strong interpersonal mechanisms, such as teacher-student relationships (Foster, 1990(Foster, , 1998Lomotey, 1989Lomotey, , 2003Tillman, 2004;Walker, 1996Walker, , 2000. Postdesegregation schools designed for…”
Section: The Relational Work Of Black Educatorsmentioning
confidence: 99%
“…E. Morris, 1999). Supportive Black educator-student relationships have also been found in all-Black classrooms within racially heterogeneous school environments (e.g., McKinney de Royston et al, 2017) as well as between Black educators and Black students that interact within racially heterogeneous classrooms and schools (Ladson-Billings, 1995Milner, 2006) This literature makes clear that Black educator-Black student relationships are historically and politically situated mechanisms of interpersonal care that support the well-being, academic achievement and long-term success of Black students (e.g., Anderson, 1988;Beauboeuf-Lafontant, 1999;Dixson, 2003;Foster, 1998;Irvine, 1989;Ladson-Billings, 2005;Tillman, 2004;Walker, 1996). This relational work is often rooted in Black educators' clarity about the historical and political landscape they and their students work, worship, and otherwise live within daily.…”
Section: The Relational Work Of Black Educatorsmentioning
confidence: 99%
“…feminist theories in women's leadership studies from Brunner 1998;Grogan 1996;Lumby 2008), racism from Gooden 2012;Tillman 2004). Drawing on radical humanist and radical structuralist versions of critical theory (e.g.…”
Section: Critical Transformative Oriented Approachesmentioning
confidence: 99%
“…Educational leadership research, even with its history of omitting non-dominant perspectives and scholarship (Gooden, 2012), can serve as a useful example for how scholars of color have articulated research that has pushes back against the ills of a post-truth era. For example, Tillman (2004) found that education research journals had a long history of placing the study of Black issues and Black leaders at the margins. The research literature on educational leadership has had a troubled past of limiting the voices and perspectives of scholars of color (Dantley, 1990(Dantley, , 2002Tillman, 2004).…”
Section: Lessons From Educational Leadershipmentioning
confidence: 99%
“…For example, Tillman (2004) found that education research journals had a long history of placing the study of Black issues and Black leaders at the margins. The research literature on educational leadership has had a troubled past of limiting the voices and perspectives of scholars of color (Dantley, 1990(Dantley, , 2002Tillman, 2004). However, as the field of educational leadership has been slow to include voices of alternative perspectives within its discourse (Dantley, 2003;Dantley & Rogers, 2001), the past 30 years has seen an emergence of research from scholars of color.…”
Section: Lessons From Educational Leadershipmentioning
confidence: 99%